Implementasi Metode Prototype Pada Proses PPDB dan Konsultasi Penjurusan (Studi Kasus: SMK Muhammadiyah 3 Yogyakarta) - Afifah, Qonita; Mardhia, Murein Miksa (Prodi Sistem Informasi Universitas Dharma Andalas, 2025)
The development of information technology requires schools to optimize the system to improve efficiency, including in the process of admitting new students (PPDB). Muhammadiyah 3 Yogyakarta Vocational Highschool still uses manual PPDB methods such as data collection and processing which causes inefficiency in the registration process, data errors, and requires a lot of energy from the school. This research aims to develop a website-based PPDB system that is tailored to the needs of the school. Data was collected through interviews, observations, and literature studies, with a prototype method approach that involved schools at every stage of development. System testing using usability tests and User Experience Questionnaire (UEQ) with the results of the online PPDB system obtained a positive response with a score of “Excellent” in the aspects of Attractiveness (1.89) and Stimulation (1.81), as well as “Good” in the aspects of Efficiency (1.87), Dependability (1.58), and Novelty (1.57) showing a significant improvement in the quality of the PPDB system of Muhammadiyah 3 Yogyakarta Vocational Highschool.